Non-Traditional Methods of Teaching Foreign Languages - Ruziyeva Komila Yangiboevna (Genius Journals, 2022)
The principle of success in the process of learning a foreign language is the most important principle and condition for constantly maintaining interest in learning a subject. This is all the more important when teaching a foreign language in ASO conditions, when the loss of motive due to failure harms the learning process as a whole. However, it should be noted that the ASO model itself, when used correctly, always guarantees the successful formation of communicative competence, since the density of work simply makes it impossible to fail.
Keywords: Suggestopedic method; Two-dimensionality; Consciously-practical method; Explicit methods